Randomised trial of two pharmacological methods of bowel preparation for day case colonoscopy. Issue 2 (1st February 1999) - Pinfield, Anne; Stringer, Mark D
Abstract : AIMS: To undertake a prospective, single blind, randomised trial comparing the efficacy and tolerance of two outpatient colonoscopy bowel preparation regimens. METHODS: Patients aged between 18 months and 16 years being admitted for day case colonoscopy were allocated randomly to receive either Picolax (an oral, sugar free powder containing sodium picosulphate 10 mg/sachet with magnesium citrate) and clear fluids or bisacodyl tablets with an unrestricted diet and a phosphate enema just before colonoscopy. Patient compliance, bowel frequency, and associated symptoms were recorded, and the adequacy of the bowel preparation was assessed in a blinded manner. RESULTS: 63 of 66 patients completed the trial. Mean age, mean weight, extent of colonoscopy, and distribution of underlying pathology were similar in both groups. Bowel preparation was good or excellent in all of the patients in the Picolax group (n = 32) compared with 22 patients in the bisacodyl/phosphate enema group (n = 31). The latter group experienced more abdominal discomfort during bowel preparation but three of the Picolax group vomited and the lack of solid food distressed some children. CONCLUSIONS: All bowel preparation methods have limitations and unpleasant side effects but the use of Picolax and clear fluids proved superior to bisacodyl tablets and a phosphate enema in children undergoing day case colonoscopy.